Herbal Medicine: A Potential Therapeutic Approach for Breast Cancer in Near Future - Veerappa Hugar; Daneshwari S Kanashetti; Nayan Kamal Dwevedi (Journal of Pharmaceutical Research)
The use of naturally occurring compounds to stop carcinogenesis is expanding. It has been shown that a variety of herbal extracts and pure active compounds produced exclusively from plants have potent anti-cancer properties. Herbs can play a supportive role in promoting complete recovery, alleviating side effects, and addressing cancer-related issues. Haridra- Curcuma longa, Guduchi- Tinospora cordifolia, Atasi- Linum ussitatissimum, Kalajaji- Nigella sativa, Lashuna- Allium sativum, Ashwagandha- Withania somnifera, Kalamegha- Andrographis paniculata, Trapusha- Podophyllum hexandrum, Shigru- Moringa ptyrygosperma,Bhumyalaki- Phyllanthus niruri, Pippali- Piper longum etc. are various plants having scientific evidence of anticancer property.Numerous in vitro and in vivo studies have suggested that these medications have potential for treating breast cancer. Studies focused on molecular pathways have aided in the discovery of the main therapeutic strategies for treating breast cancer. The focus of future research should be on patient-centered translational trials for breast cancer. These will strengthen the therapeutic effectiveness of our Ayurvedic medication. This review seeks to offer experimental support and a greater understanding of the molecular processes by which various herbs function as chemotherapeutic agents against distinct forms of breast cancer. Keywords Anti-cancer, Ayurvedic herbs, Plant based medicine, Breast cancer